Tren Terkini dalam Dunia Pendidikan - Ainul Yaqin, Mokhammad (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
The trend of Information Technology which is getting more rapid in the current era of globalization cannot be avoided anymore its impact on the world of education. This is because it has several advantages, including learning resources that are easier to find benefits in the world of education such as media and multimedia and e-learning, Blended learning, Ubiquitous Learning and others which have the benefit of increasing the motivation of students in learning activities. Thus, educators can determine the variation of learning as desired by students. In addition, there are obstacles to implementing Information Technology in education in Indonesia, namely the lack of availability of facilities and infrastructure. Information technology owned by educational institutions, in addition to development and procurement costs related to information technology infrastructure, has not been provided maximally by the government.To overcome these obstacles, it is necessary to have commitment and seriousness to apply Information Technology for education from the government and it is an important decision to answer and ensure the availability of information technology for our world of education so that we are no longer left behind with other countries.